Behavioral Finance Factors Influencing Investment Decisions Among Generation Z Investors - Irdawati Irdawati; Rihfenti Ernayani; Sarni Handayani Puspita Sari; Klemens Mere (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
The rapid growth of digital financial technology has significantly increased the participation of young investors, particularly Generation Z, in financial markets. However, investment decisions made by this generation are often influenced not only by rational financial analysis but also by psychological and behavioral factors. This study aims to examine behavioral finance factors that influence investment decisions among Generation Z investors. The study focuses on key behavioral aspects such as overconfidence bias, herding behavior, loss aversion, risk perception, and financial literacy, which are widely recognized as important determinants of individual investment behavior. This research employs a systematic literature review method to analyze relevant academic studies related to behavioral finance and investment decision-making. Data were collected from scholarly databases such as Google Scholar, Scopus, Web of Science, and ScienceDirect. The selected literature was analyzed to identify key themes, theoretical frameworks, and empirical findings regarding behavioral biases affecting investment decisions. The findings indicate that behavioral factors significantly influence the investment decisions of Generation Z investors. Overconfidence and herding behavior often lead investors to rely on personal judgment or market trends rather than objective analysis. In addition, loss aversion and risk perception affect how investors respond to potential gains and losses. Financial literacy is also found to play a crucial role in helping investors make more rational and informed investment decisions.